2021
DOI: 10.1016/j.gore.2021.100810
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare provider challenges to early detection of cervical cancer at primary healthcare level in Rwanda

Abstract: Highlights Cervical cancer is the fourth most common cancer in women despite being a preventable disease. Both patient and health system factors contribute to delay in diagnosis. Lack of knowledge and facilities create a gap in cervical cancer screening and prevention services. Coordinated effort is needed to integrate a functional cervical cancer prevention program into the Rwandan health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…At the healthcare provider level, healthcare providers' adherence to screening guidelines, and their advice played a significant role in motivating and encouraging eligible women to undergo screening which is consistent with a study that identified encouraging women to have CCS increases the uptake [81]. However, there were also barriers reported by providers, such as fragmented services, a lack of staff, insufficient training, increased workloads, and prioritizing curative healthcare which is supported by other studies [65,82,83]. These barriers shed light on the need to ensure adequate staffing, resources, training, and institutional support for healthcare providers to integrate cervical cancer screening effectively.…”
Section: Discussionsupporting
confidence: 76%
“…At the healthcare provider level, healthcare providers' adherence to screening guidelines, and their advice played a significant role in motivating and encouraging eligible women to undergo screening which is consistent with a study that identified encouraging women to have CCS increases the uptake [81]. However, there were also barriers reported by providers, such as fragmented services, a lack of staff, insufficient training, increased workloads, and prioritizing curative healthcare which is supported by other studies [65,82,83]. These barriers shed light on the need to ensure adequate staffing, resources, training, and institutional support for healthcare providers to integrate cervical cancer screening effectively.…”
Section: Discussionsupporting
confidence: 76%
“…In focus group interview, we used a semi-structured interview guide 22 with 9 open ended questions with possibility of probing as needed ( Supplementary Material S1 ) and conducted face-to-face interview with recording of voices. The choice for focus group interview was based on the fact that most of existing qualitative research related to cervical cancer screening in Rwanda have used structured questionnaires or questions with yes/no answers 18 , 23 , 24 therefore, to be able to collect in depth subjective opinions 22 , 25 from primordial potential beneficiary of cervical screening we opted for focus group interview. One team of facilitators conducted interview for all five focus groups.…”
Section: Methodsmentioning
confidence: 99%
“…The Rwandan study reported an absence of association between knowledge and specialty, education level, or work experience. 50 Specialty of practice and years of experience were significantly associated with knowledge about HPV as per Almazrou, 51 among physicians in Saudi Arabia. However, according to Chawla et al, 38 age, specialty of practice, and years of experience were associated with knowledge, but no difference was noted between genders.…”
Section: Discussionmentioning
confidence: 93%